Deep-learning based detection of vessel occlusions on CT-angiography in patients with suspected acute ischemic stroke - Brugnara, Gianluca; Baumgartner, Michael; Scholze, Edwin; Deike-Hofmann, Katerina; Kades, Klaus; Scherer, Jonas; Denner, Stefan; Meredig, Hagen; Rastogi, Aditya; Mahmutoglu, Mustafa A.; Ulfert, Christian; Neuberger, Ulf; et al. (Nature Communications, 2023)
Swift diagnosis and treatment play a decisive role in the clinical outcome of patients with acute ischemic stroke (AIS), and computer-aided diagnosis (CAD) systems can accelerate the underlying diagnostic processes. Here, we developed an artificial neural network (ANN) which allows automated detection of abnormal vessel findings without any a-priori restrictions and in <2 minutes. Pseudo-prospective external validation was performed in consecutive patients with suspected AIS from 4 different hospitals during a 6-month timeframe and demonstrated high sensitivity (≥87%) and negative predictive value (≥93%). Benchmarking against two CE- and FDA-approved software solutions showed significantly higher performance for our ANN with improvements of 25-45% for sensitivity and 4-11% for NPV (p ≤ 0.003 each). We provide an imaging platform (https://stroke.neuroAI-HD.org) for online processing of medical imaging data with the developed ANN, including provisions for data crowdsourcing, which will allow continuous refinements and serve as a blueprint to build robust and generalizable AI algorithms.